2016
DOI: 10.1021/acs.orglett.5b03473
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Semisynthesis of a Segetane Diterpenoid from a Jatrophane Precursor via a Diels–Alder Reaction

Abstract: A novel segetane diterpenoid (1) and four jatrophane diterpenoids (2-5) were isolated from an acetone extract of Euphorbia peplus. Due to quantity limitations, we prepared 1 via a Diels-Alder reaction, an approach motivated by this compound's biosynthetic pathway and successfully performed X-ray analysis of 1. Furthermore, in an in vitro activity test, 1 exhibited moderate anti-inflammatory activity, whereas both its precursor (2) and the relevant intermediate (2a, IC50 = 1.56 μM) exhibited significant anti-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
0
20
1
Order By: Relevance
“…Unlike the aforementioned biosynthesis proposed by and previously by Jakupovic et al (1998a, b, c) that the segetane tetracyclic skeleton was formed by a two-steps cyclization of jatrophane derivative, Wan et al (2016b) found that an intermediate with four double bonds is a precursor of segetanes. Through this biosynthetic pathway, the intermediate bearing four double bonds is formed by an elimination reaction on a proper jatrophane; after that this intermediate can be transformed into a segetane via a Diels-Alder reaction in the presence of a Lewis base and/or a Lewis acid (Fig.…”
Section: Segetane Diterpenoidscontrasting
confidence: 72%
See 1 more Smart Citation
“…Unlike the aforementioned biosynthesis proposed by and previously by Jakupovic et al (1998a, b, c) that the segetane tetracyclic skeleton was formed by a two-steps cyclization of jatrophane derivative, Wan et al (2016b) found that an intermediate with four double bonds is a precursor of segetanes. Through this biosynthetic pathway, the intermediate bearing four double bonds is formed by an elimination reaction on a proper jatrophane; after that this intermediate can be transformed into a segetane via a Diels-Alder reaction in the presence of a Lewis base and/or a Lewis acid (Fig.…”
Section: Segetane Diterpenoidscontrasting
confidence: 72%
“…10). The study of the generalization of this reaction proved that the presence of a carbonyl at C-9 and lack of substitution at C-8 are indispensable to the formation of a segetane skeleton from a jatrophane skeleton (Wan et al 2016b).…”
Section: Segetane Diterpenoidsmentioning
confidence: 97%
“…Compound 4 was proven to be 5-acetoxy-3,9-dicinnamoyloxy-15-hydroxy-14-oxo-jatropha-6(17),11E-diene, previously described only from E. segetalis [22]. 1 Segetanes represent a peculiar and rare class of diterpenes, only 12 compounds have been described from E. paralias, E. segetalis, Euphorbia portlandica, and Euphorbia peplus, to date [21,22,24,[26][27][28][29]. According to an earlier classification, E. taurinensis and E. peplus were considered to be members of section Cymatospermum (Prokh.)…”
Section: Resultsmentioning
confidence: 99%
“…, benzoyl, acetyl, nicotinoyl, butanoyl and isobutyryl). Meanwhile, jatrophanes exert a wide variety of biological activities, such as the ability to modulate of P-glycoprotein (ABCB1) 3 , 4 , 5 , 6 as well as antiproliferative 7 , 8 , antimalarial 9 , anti-inflammatory 10 , and antiviral 11 activities. From a biosynthetic perspective, jatrophanes are regarded as precursors to presegetanes, segetanes, paralianes, and pepluanes because these diterpenoids can be derived from an intramolecular cyclization of the 12-membered macrocycle of the jatrophane diterpenoids 10 , 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%